IRON CHELATION THERAPY IN THALASSEMIA SYNDROMES - Paolo Cianciulli (Mediterranean Journal of Hematology and Infectious Diseases)
Transfusional hemosiderosis is a frequent complication in patients with transfusion dependent chronic diseases such as  thalassemias and severe type of sickle cell diseases. As there are no physiological mechanisms to excrete the iron contained in transfused red cells (1 unit of blood contains approximately 200 mg of iron) the excess of iron is stored in various organs. Cardiomyopathy is the most severe complication covering more than 70% of the causes of death of thalassemic patients. Although the current reference standard iron chelator deferoxamine (DFO) has been used clinically for over four decades, its effectiveness is limited by a demanding therapeutic regimen that leads to poor compliance. Despite poor compliance, because of the inconvenience of subcutaneous infusion, DFO improved considerably the survival and quality of life of patients with thalassemia. Deferiprone since 1998 and Deferasirox since 2005 were licensed for clinical use. The oral chelators have a better compliance because of oral use, a comparable efficacy to DFO in iron excretion and probably a better penetration to myocardial cells. Considerable increase in iron excretion was documented with combination therapy of DFO and Deferiprone. The proper use of the three chelators will improve the prevention and treatment of iron overload, it will reduce  complications, and improve survival and quality of life of transfused patients